The Effect of Work Environment, Transformational Leadership Style, and Principal Management Skill Towards Teacher Performance: The Role of Teacher Competency as A Mediation Variable - Mulyadi, Mulyadi; Helty, Helty; Vahlepi, Sahrizal; Sastrawati, Eka (JETL (Journal of Education, Teaching and Learning), 2024)
This study aims to examine the effect of the work environment, transformational leadership style, and managerial skills of principals on teacher performance: the role of teacher competence as a mediating variable. This study uses a quantitative approach. This type of research is explanatory research that seeks to determine the causal relationship between variables. The data collection method in this study uses survey method with the sample used is total sampling because the total population is < 100 respondents. The data analysis technique in this study uses path analysis assisted by Smart PLS application. Based on the test results, it is known that work environment and managerial skills of the principal have a positive and significant effect on teacher performance and competence. Meanwhile, the transformational leadership style has not been able to influence competence and performance. In addition, it is known that teacher competence is able to mediate the relationship between the work environment, transformational leadership style, and managerial skills of principals on teacher performance. The findings in this study can be used as a basis for educational supervision to find solutions in an effort to improve the quality of education and can provide awareness for leaders in educational institutions, namely schools that their role in managing an institution will affect the performance of employees, especially teachers.